MoS2 Nanosheets Assembled on Three-Way Nitrogen-Doped Carbon Tubes for Photocatalytic Water Splitting - Zhang, Yujia; Liu, Yan; Gao, Wen; Chen, Ping; Cui, Hongyu; Fan, Yanfei; Shi, Xifeng; Zhao, Yingqiang; Cui, Guanwei; Tang, Bo (Frontiers in Chemistry, 2019)
In this work, a micron-sized three-way nitrogen-doped carbon tube covered with MoS2 nanosheets (TNCT@MoS2) was synthesized and applied in photocatalytic water splitting without any sacrificial agents for the first time. The micron-sized three-way nitrogen-doped carbon tube (TNCT) was facilely synthesized by the calcination of commercial sponge. The MoS2 nanosheets were assembled on the carbon tubes by a hydrothermal method. Compared with MoS2, the TNCT@MoS2 heterostructures showed higher H2 evolution rate, which was ascribed to the improved charge separation efficiency and the increased active sites afforded by the TNCT.